2019
DOI: 10.1049/iet-rpg.2019.0159
|View full text |Cite
|
Sign up to set email alerts
|

Distributed load management scheme to increase PV hosting capacity in LV feeders

Abstract: Proliferation of photovoltaic (PV) panels may cause voltage increases in low voltage (LV) distribution feeders. This issue confines PV hosting capacity of the feeders. To overcome this issue and enable higher PV hosting capacity, a model to manage the operation cycles of the domestic electric water heater and heating, ventilation, and air conditioning loads in order to avoid the voltage rise, thereby increasing PV hosting capacity in LV feeders is presented in this study. The model respects users' thermal comf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Rahman et al [15] showed that a control scheme using DR and OLTC efficiently improves HC in suburban LV networks in Australia. In [28], the authors proposed a distributed load management scheme for HC improvement using heating, ventilation, and air conditioning (HVAC) loads, electric water heater, and two-way communication. All previous RDR studies for HC improvement use the DLC scheme.…”
Section: Related Workmentioning
confidence: 99%
“…Rahman et al [15] showed that a control scheme using DR and OLTC efficiently improves HC in suburban LV networks in Australia. In [28], the authors proposed a distributed load management scheme for HC improvement using heating, ventilation, and air conditioning (HVAC) loads, electric water heater, and two-way communication. All previous RDR studies for HC improvement use the DLC scheme.…”
Section: Related Workmentioning
confidence: 99%
“…Similarly, an improved HC along with reduced network losses has been observed in [71] by the utilization of the residential DR in tandem with OLTC in a suburban radial LV Australian network with a penetration of 35% of the transformer capacity (65 kW). The authors investigated a single-phase LV distribution feeder with two-way communication supplying 10 loads in [123]. The operations of Heating, Ventilation, and Air Conditioning (HVAC) loads and Electric Water Heater (EWH) are managed in such a way to achieve voltage regulation without compromising the thermal comfort of the customers.…”
Section: Demand Responsementioning
confidence: 99%
“…According to the literature review, a fair range of studies have been carried out globally to examine feasible solutions that could be adopted to enhance PV uptake [10][11][12][13][14][15][16][17][18][19][20]. However, most of the studies are focused on advanced control approaches where a significant amount of infrastructure upgrades and maintenances are required to secure the efficiency.…”
Section: Introductionmentioning
confidence: 99%